PENGARUH PRICE EARNING RATIO, DEVIDEN PAYOUT RATIO, DAN RETURN ON EQUITY TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Refi Cipta Fidrian; Abdul Qodir Djaelani; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT“The purpose of this research are: 1) to find out the Price Earning Ratio (PER) and how it affects to the company’s stock prices of manufacture companies 2) to understand the influence of Dividend Payout Ratio (DPR) towards the company’s stock prices of manufacture companies 3) to discover the impact of Return On Equity (ROE) towards company’s stock prices of manufacture companies. The population of this research are manufacture companies that listed on the Indonesia Stock Exchange in 2015-2017. The method that is used to analyze by the multiple linear regression test with a t-test as the hypothesis tester. The result of this research has proved that the Price Earning Ratio (PER) has brought a negative influence and not significantly while the Dividend Payout Ratio (DPR) also has a negative influence and not significant. However, the Debt to Equity Ratio (DER) has a positive impact and significantly”.Keywords : Return Stock, Price Earning Ratio (PER), Dividend Payout Ratio (DPR), and Return On Equity (ROE).